DERABBIZATION, POLITICAL DEVELOPMENT, ECONOMICS, GOVERNMENT ADMINISTRATION, EDUCATION AND LAW IN THE ABBASID ERA - Aminol Rosid Abdullah (Journal of Islamic and Interdisciplinary Research, 2025)
This study uses a Literature Review (SLR) approach to explore the concept of Dearabization and the development of politics, economics, government administration, education, and law during the Abbasid era as the golden period of Islamic civilization. The study was conducted by collecting, analyzing, and synthesizing various primary and secondary sources in the form of books, journals, and relevant historical archives. Dearabization is understood as a process of expanding the Islamic cultural space that is no longer focused on Arab ethnic domination, but rather opens up opportunities for the integration of non-Arab nations, thereby accelerating intellectual and government dynamics. In the context of politics and government administration, a more organized bureaucratic structure emerged with the contribution of the Persian nation, while the economy developed rapidly through international trade and agricultural progress. Education gave birth to scientific institutions such as the Baitul Hikmah which became centers of translation and scientific study, while the legal field experienced a systematic codification of fiqh. Literature findings indicate that Dearabization actually strengthened Islamic civilization and led the Abbasid era to become a center of global progress. The implications of these findings for the development of contemporary Islamic civilization lie in inspiring adaptive, just, and knowledge-based governance. The Abbasid principle of derabbanization offers lessons on the separation of functions, bureaucratic professionalism, strengthening a productive economy, and inclusive education all of which align with modern challenges such as plurality, innovation, and accountability.